Sudden Cardiac Arrest and Rare Genetic Variants in the Community. (April 2016) - Milano, Annalisa; Blom, Marieke T.; Lodder, Elisabeth M.; van Hoeijen, Daniel A.; Barc, Julien; Koopmann, Tamara T.; Bardai, Abdennasser; Beekman, Leander; Lichtner, Peter; van den Berg, Maarten P.; Wilde, Arthur A.M.; Bezzina, Connie R.; et al.
Abstract : Background—: Sudden cardiac arrest (SCA) ranks among the most common causes of death worldwide. Because SCA is most often lethal, yet mostly occurs in individuals without previously known cardiac disease, the identification of patients at risk for SCA could save many lives. In unselected SCA victims from the community, common genetic variants (which are not disease-causing per se, but may increase susceptibility to ventricular fibrillation) are found to be associated with increased SCA risk. However, whether rare genetic variants contribute to SCA risk in the community is largely unexplored. Methods and Results—: We here investigated the involvement of rare genetic variants in SCA risk at the population level by studying the prevalence of 6 founder genetic variants present in the Dutch population (PLN-p.Arg14del, MYBPC3-p.Trp792fsX17, MYBPC3-p.Arg943X, MYBPC3-p.Pro955fsX95, PKP2-p.Arg79X, and the Chr7q36 idiopathic ventricular fibrillation risk haplotype) in a cohort of 1440 unselected Dutch SCA victims included in the Amsterdam Resuscitation Study (ARREST). The six studied founder mutations were found to be more prevalent (1.1%) in the ARREST SCA cohort compared with an ethnically and geographically matched set of controls (0.4%, n=1379; P <0.05) or a set of Dutch individuals drawn from the Genome of the Netherlands (GoNL) study (0%, n=500; P <0.02). Conclusions—: This finding provides proof-of-concept for the notion that rare genetic variants contribute to some extent to SCA risk in the community. Abstract : Supplemental Digital Content is available in the text.